Water erosion at different slope lengths - Rodrigues, Sonia Armbrust; Bertol, Ildegardis; Bagio, Bárbara; Wolschick, Neuro Hilton; Bernardi, Loriane; Oliveira, Marco Fruhauf de; Fehlauer, Tércio Vaisnava (Delos (Málaga), 2024)
Water erosion is strongly influenced by slope length (Sl), among other factors. The objective of this work was to quantify the water losses (WL) and soil losses (SL) in different Sl, in a Haplic Distrudept. These losses were determined during one year in uncultivated and uncovered soil (BS) and then in soil cultivated in the form of no-tillage (NT) during three cropping cycles, under natural rainfall conditions. The treatments, with one repetition, consisted of the Sl of 11 m, 22 m, 33 m, and 44 m with 8% slope. In the 1st cycle, black oat (Avena strigosa) + forage radish (Raphanus sativus) + common vetch (Vicia sativa) was cultivated, in the 2nd cycle, single black bean (Phaseolus vulgaris) and in the 3rd cycle, single black oat. With the increase of Sl in the interval from 11 to 44 m, the WL and SL increased, and the SL increased with the increase of the WL. WL and SL were explained by Sl in 79% and 99%, respectively, and SL were explained in 76% by WL. The y = a + bx model was fitted to the data (p<0.01). Soil crop for one year in the form of NT reduced WL by 30% and SL by 99% compared to the losses that occurred in the condition in which the soil was under BS. The WL varied less than the SL, in the range from 11 to 44 m of slope.